ZDQ-0620, a Novel Phosphatidylinositol 3-Kinase Inhibitor, Inhibits Colorectal Carcinoma Cell Proliferation and Suppresses Angiogenesis by Attenuating PI3K/AKT/mTOR Pathway - Qin, Xiaochun; Liu, Mingyue; Xu, Chang; Xing, Bo; Xu, Xiangbo; Wu, Yuting; Ding, Huaiwei; Zhao, Qingchun (Frontiers in Oncology, 2022)
The PI3K/AKT pathway plays a central role in human cancers, aberrant activation of this pathway is associated with tumorigenesis, cancer progression and angiogenesis. Based on the importance of the PI3K/AKT pathway in malignancies, we developed a 4-aminoquinazoline derivative, ZDQ-0620, initially envisioned as a novel pan-PI3K inhibitor. This study aimed to evaluate the potential target of ZDQ-0620 and its anticancer effect in human colorectal carcinoma (CRC). PI3K-kinase activity test showed IC50 of ZDQ-0620 against PI3Ka was 0.5 nM; molecular docking, CETSA assay and western blotting was further performed to predict ZDQ-0620 was a PI3K/AKT pathway inhibitor by targeting PI3K. To identify the effect of ZDQ-0620 on CRC cells, Sulforhodamine B (SRB) assay, flow cytometry, and Cell morphology analysis were conducted. The results showed that ZDQ-0620 inhibited the proliferation, migration and invasion of CRC cells, induced apoptosis through G0/G1 cell cycle arrest and mitochondrial pathway. Additionally, ZDQ-0620 inhibited the migration and tube formation of human umbilical vein endothelial cells (HUVECs). In vivo, neovascularization of rat aortic ring and chick chorioallantoic membrane (CAM) induced by VEGF was diminished when treated with ZDQ-0620. These results indicate that ZDQ-0620 induce apoptosis and anti-angiogenesis via inhibits the PI3K/AKT pathway. We suggest that the great potential of ZDQ-0620 as an effective treatment candidate against CRC.